"If competition has any virtue, we ought not to have a system that stifles it": Competition in London Clearing Banking, 1946–1971. (16th September 2021) - ARCH, LINDA
Abstract : Concentration in many industries has increased markedly in recent decades in the United States, although in Europe it has been stable or has even decreased. Where concentration has increased, the question arises as to how to measure the extent of competition (or the degree to which it is contestable) in a market in which there are relatively few competing firms, over the long term. This article explores competition in clearing banking in the UK from 1946 to 1971. This period is of interest in the context of industry concentration because clearing banking was relatively concentrated and, it has long been argued, uncompetitive. The article evaluates competition from four perspectives. First, it considers the competitiveness of London clearing banking from a quantitative perspective. Next, it evaluates competition through the lens of competition policy, particularly the extent to which monopoly, mergers, and restrictive trade practices existed in clearing banking. Third, the conclusions of the National Board for Prices and Incomes' report into bank charges in 1967 are considered. Finally, it explores the extent to which the clearing banks were open to and embraced change, and were innovative, assuming that these qualities are more likely to be present when there is competition among banks. It questions key aspects of the dominant interpretation of clearing banking as uncompetitive and slow to innovate.